Multitemporal evaluation of the vegetation cover of the Tapirapé biological reserve, Pará (Research, Society and Development, 2021)
The present work seeks to analyze the multitemporality of the Tapirapé Biological Plant Cover (REBIO) in the years 2013 and 2018. For digital processing, images from the Landsat 8 satellite of 06/14/2013 and 08/03/2018, OLI spectral sensor were used. and thermal TIRS the reference datum WGS 1984 and in the spindle 22S the procedures used the software ArcGis 10.5. In order to carry out the NDVI, the values were grouped into four classes: water bodies, exposed soil, open rainforest and closed rainforest and their respective surface targets identified by the change in reflectance, so that the closer to +1, the greater the density vegetation and when close to -1 less dense. The results showed a difference in vegetation cover over the years. Class 1 showed negative values of (-0.16) and (-0.18) not reflected due to the Tapirapé river compared to 2013 there was an increase of 23.7% in the presence of bodies of water in the reserve. Class 2 with a 0.31 reflectance value, with a decrease of 5.8% in exposed soil in 2018. Class 3 (0.44) showed 1.5% growth of undergrowth. Class 4, expressed an increase of 1% in vegetation.